Foot and ankle injuries in surfing, windsurfing, Kitesurfing: A follow up study and review of the literature - Kristen, K.-H. (Sport-Orthopädie - Sport-Traumatologie, 2018)
Water sports appear to be save concerning foot and ankle injuries. However, analyzing injury patterns in Windsurf, Kitesurf and wave surf, foot and ankle injuries rate within the most frequent injuries. Collision with the board, obstacles in the water close to the beach and rotation trauma with the foot fixed in foot straps and bindings are the main causes. Reef cuts and open wounds may cause dangerous infections especially in tropical water. Midfoot injuries may cause painful chronic instability and arthritis. Lisfranc joint lesions and subtalar injuries must be excluded after a fall with the foot caught in the foot strap.